Adaptasi Dan Interaksi Mahasiswa Pattani (Thailand) Dalam Tinjauan Komunikasi Antar Budaya Di Lampung - Atika Fadilatul Rodiyah Saputri; Muhamad Bisri Mustofa; Siti Wuryan (Jurnal Peurawi: Media Kajian Komunikasi Islam, 2021)
Intercultural communication will occur if there is communication between each other who has different backgrounds. When someone has a different culture and background, it is possible that the barriers to communication will increase. Likewise, what was experienced by Pattani students who were studying at the Raden Intan State Islamic University Lampung, when there was communication with local students who had various cultures, of course, they encountered many obstacles. Communicators who are involved in the interaction certainly want effective communication between each other. Therefore, Pattani students are required to be able to adapt and acculturate the existing culture to reduce uncertainty. Qualitative descriptive is the type of research used in this scientific work. Based on the data seen in the field, a common thread can be drawn, that Pattani (Thailand) students have 2 ways of interacting, namely: verbal and nonverbal communication.